Mightier than the sword - Archer, Jeffrey (New York St. Martin's Press, 2015)
When Harry arrives in New York, his publisher Harold Guinzberg tells him he has been elected as the next president of English PEN, which will give him the opportunity to launch a campaign for the release of a fellow author, Anatoly Babakov, who is languishing in a Russian Gulag in Siberia. His crime: writing a book Uncle Joe, which gives an insight into what it was like to work for Josef Stalin. So determined is he to see Babakov released, Harry puts his own life in danger. Emma Clifton, now Chairman of Barrington Shipping, is having to face the repercussions of the IRA bombing her ship. Some board members feel she should resign while others, including Sebastian Clifton, newly elected to the board, are determined to see she remains as Chairman. Giles Barrington is now a Minister of the Crown, and looks set for high office, but a trip to East Germany does not end as a diplomatic success, and once again Giles' political career is thrown off balance by none other than Major Alex Fisher. Fisher decides to stand against Giles at the forthcoming general election. But this time who wins?
103062
Keywords: Families -- England -- History -- 20th century; Social classes -- England; England; Great Britain; Fiction; History; Historical fiction; Domestic fiction